Adjusted macroeconomic indicators to account for ecosystem degradation: an illustrative example. Issue 1 (2nd January 2019) - La Notte, Alessandra; Marques, Alexandra
ABSTRACT: Adjusting macroeconomic indicators to account for the depletion and degradation of natural capital has long been viewed as a way to show the linkages between nature and the economy and foster more sustainable paths of development. Here, we show how the System of Environmental Economic Accounting (SEEA) Experimental Ecosystem Accounting (EEA) can be used to develop environmentally adjusted macroeconomic indicators. More specifically, we show how an enlargement of the production boundary to include the consideration of ecosystems as institutional units allows the development of a net value added metric that reflects depreciation and degradation of the natural capital assets. This measurement could be useful for policymaking: the linkage of ecosystem services to economic activities allows us to account for loss, repair and substitution of natural capital, and thus helps us to formulate and monitor environmental policies.